2020
DOI: 10.1515/helia-2020-0025
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of change in broomrape populations (Orobanche cumana Wallr.) in Romania and Russia (Black Sea area)

Abstract: The emergence of new broomrape populations (races) has been observed in the past 20 years in several countries (Romania, Moldova, Ukraine, Russia, Turkey, Bulgaria, Spain, Serbia, and China) where sunflower is frequently grown in the same sites without applying traditional crop rotations. Differential lines for sunflower broomrape races A to F have been secured. The new broomrape races have been identified by researchers as races G and H. The question of whether the same broomrape mutations can occur in one ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The race evolution of sunflower broomrape is primarily driven by mutations, consistent with the gene-for-gene host-parasite interaction between this parasite and the sunflower crop (Rodrıǵuez-Ojeda et al, 2013;S ̌korićet al, 2021). Genetic recombination between avirulence loci has also been proposed as an additional mechanism for race evolution in this species (Martıń-Sanz et al, 2016).…”
Section: Discussionmentioning
confidence: 60%
“…The race evolution of sunflower broomrape is primarily driven by mutations, consistent with the gene-for-gene host-parasite interaction between this parasite and the sunflower crop (Rodrıǵuez-Ojeda et al, 2013;S ̌korićet al, 2021). Genetic recombination between avirulence loci has also been proposed as an additional mechanism for race evolution in this species (Martıń-Sanz et al, 2016).…”
Section: Discussionmentioning
confidence: 60%
“…Investigation of broomrape virulence from sunflower growing countries is important to guide the breeding and selection of tolerant varieties for effectively managing O. cumana ( Perez-de-Luque et al., 2009 ; Shi and Zhao, 2020 ). Over the years, several surveys have been conducted from broomrape samples collected from Spain, Turkey, Romania, Bulgaria, Serbia and Russia ( Malek et al., 2017 ; Škorić et al., 2021 ). Here, the racial evaluation of the two Greek populations to a set of differential sunflower host genotypes showed that the population from Drama belonged to race G+ while the other population from Orestiada belonged to race G. The identification of highly virulent broomrape strains from Greece is in line with a recent investigation which showed that the two races were prevalent in most South-eastern European countries except for Serbia whereby the strains were found to belong to race E or were less virulent than E ( Duca et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%